Medical student syndrome between clarity and ambiguity - Hussein, Hend M.; Aljazaeri, Manar A.; Zulali, Hala R.; Alrahule, Shiyma A.; Bakr, Omama M. Abu; Alhawsawi , Duaa I. (International Journal Of Community Medicine And Public Health, 2025)
Background: Medical student syndrome (MSS) is a unique form of hypochondriasis observed in medical students, characterized by preoccupation with fears of having serious diseases based on misinterpreting bodily symptoms despite medical reassurance. Unlike hypochondriasis, MSS does not result in increased consultations. This phenomenon varies in prevalence among medical students compared to other health sciences students who do not study diseases as intensely. This study explores awareness of MSS and the prevalence of psychosomatic symptoms among medical and health sciences students in Saudi Arabia. Methods: A cross-sectional study was conducted using online and face-to-face questionnaires, employing multistage and cluster sampling methods. Results: The overall number of students collected is 383 students among all the medical students and other health science students the effect of MSS found higher in students of health science colleges. Conclusions: The study highlights the high prevalence of MSS among health sciences students. It emphasizes awareness and risk factors.